Calcified cephalohemtoma: A case report - Ali, Maryam Mohamed; Etbiga, Abdalla Mohamed (Journal of medical and pharmaceutical sciences, 2019)
Cephalohaematomas are traumatic subperiosteal hematomas of the skull that are usually caused by birth injury. They are bound between the periosteum and cranium, and therefore cannot cross sutures. Being bound by a suture line distinguishes them from subgaleal hematoma, which can cross sutures. Cephalohematomas occur in 1-2% of live births. The incidence increases with ventouse and forceps extraction and thus more common in primiparous mothers. There may be a greater male predilection. Cephalohaematomas are clinically diagnosed and infrequently imaged. They can be unilateral or bilateral, and appear as subgaleal fluid collections bounded by suture lines. In the setting of craniosynostosis, the blood products are able to traverse the affected suture. By 2-3 weeks, they may become peripherally calcified. The hematoma usually resolves in 2-3 months. Most resolve spontaneously. Cephalohaematomas usually gradually incorporate into the calvaria by ossification. This report describes a Libyan infant of two months of age, presented with a hard-globular swelling over the right parietal region. The child was delivered via vaginal delivery, it was a difficult delivery, at birth the cephalohemtoma was noted. The swelling was initially soft but later became hard. A suspicion that calcified cephalhematoma could present in such a manner supported by careful history taking and relevant imaging (X-ray/computed tomography) would help in appropriate evaluation of this benign condition.